Abrocitinib monotherapy in Investigator’s Global Assessment nonresponders: improvement in signs and symptoms of atopic dermatitis and quality of life - Andrew Blauvelt; Mark Boguniewicz; Patrick M. Brunner; Paula C. Luna; Pinaki Biswas; Marco DiBonaventura; Saleem A. Farooqui; Ricardo Rojo; Michael C. Cameron (Journal of Dermatological Treatment)
Background Abrocitinib, a once-daily, oral Janus kinase 1 selective inhibitor, was shown to be an effective treatment for moderate-to-severe atopic dermatitis in phase 2 b/3 monotherapy trials.Methods These analyses included data for Investigator’s Global Assessment responder (clear [0] or almost clear [1] with ≥2-grade improvement) and nonresponder patients with moderate-to-severe atopic dermatitis who received abrocitinib (200 mg or 100 mg) or placebo in three abrocitinib monotherapy trials (phase 2 b, NCT02780167; two phase 3, NCT03349060/JADE MONO-1 and NCT03575871/JADE MONO-2). Outcomes measuring skin clearance, itch, and quality of life were evaluated.Results Both nonresponders (n = 548) and responders (n = 260) treated with abrocitinib had rapid and clinically meaningful improvement in skin clearance, itch, and quality of life compared with placebo.Conclusion Patients with moderate-to-severe atopic dermatitis treated with abrocitinib who did not achieve an Investigator’s Global Assessment 0/1 response at week 12 still experienced rapid, clinically meaningful improvements across several other validated measures of efficacy and quality of life.ClinicalTrials.gov NCT02780167, NCT03349060, NCT03575871